Sosialisasi dan Pelatihan Pemanfaatan Limbah Kain Menjadi Ornamen Dekorasi Interior Rumah Tinggal di Pulau Harapan - Bambang Erwin; Margareta Maria Sudarwani; Susanti Muvana Nainggolan; Sahala Simatupang; Ulinata Ulinata (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
Community Service activities carried out by the UKI Faculty of Engineering Architecture Study Program raised the theme Green Action 28 Socialization and Training on the Utilization of Fabric Waste as Interior Decoration Ornaments for Residential Homes on Harapan Island. This activity is a continuation of the previous Community Service Activities which aim to educate the public about the design and creation of mini gardens that can be used as additional open green spaces in residential homes. The method is by holding socialization and workshops that present resource persons who are experts in their fields so that participants receive education on how to design and make Fabric Waste Into Residential Interior Decoration Ornaments so that participants can independently do it in their homes and pass it on to neighbors and their families who have never participated in outreach and training. The process is that the participants practice directly with patchwork waste brought by each participant which can be created so that it becomes an element of interior decoration in a residence so that it is more aesthetic. The training also held a question and answer session for the participants. Keywords: Green Action, Patchwork, Harapan Island